University professors’ representations on an online EMI course in Paraná - Brazil - Passoni, Taisa; Calvo, Luciana Cabrini Simões; El Kadri , Michele Salles; Stillwell, Christopher (The ESPecialist, 2024)
In Brazilian higher education institutions, English as a Medium of Instruction (EMI) courses and workshops play a key role in helping professors to rethink their methodology and their concepts of language, especially regarding English conceived as a lingua franca. In an attempt to bring a local perspective for EMI, this paper examines university professors’ representations on an online EMI course for professors from nine public universities in Paraná. It is grounded on the concept of representation from critical discourse analysis. The results reveal the beliefs and motivations of the participants concerning EMI in Brazil.